1999
DOI: 10.1021/bi990711d
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycans Interact Selectively with Chemokines and Modulate Receptor Binding and Cellular Responses

Abstract: Chemokines selectively recruit and activate a variety of cells during inflammation. Interactions between cell surface glycosaminoglycans (GAGs) and chemokines drive the formation of haptotactic or immobilized gradients of chemokines at the site of inflammation, directing this recruitment. Chemokines bind to glycosaminoglycans on human umbilical vein endothelial cells (HUVECs) with affinities in the micromolar range: RANTES > MCP-1 > IL-8 > MIP-1alpha. This binding can be competed with by soluble glycosaminogly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
554
4
5

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 525 publications
(588 citation statements)
references
References 47 publications
25
554
4
5
Order By: Relevance
“…Chemokines probably do not act as soluble entities, but as solid phase bound aggregates. Chemokines can bind proteoglycans through interactions with the glysoaminoglycan (GAG) component of the proteins [16]. The association of chemokines with GAGs of the extracelluar matrix and on the cell surface has important implications in terms of presentation and increasing local chemokine levels.…”
Section: Chemokines Are (Co)stimulatory For T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemokines probably do not act as soluble entities, but as solid phase bound aggregates. Chemokines can bind proteoglycans through interactions with the glysoaminoglycan (GAG) component of the proteins [16]. The association of chemokines with GAGs of the extracelluar matrix and on the cell surface has important implications in terms of presentation and increasing local chemokine levels.…”
Section: Chemokines Are (Co)stimulatory For T Cellsmentioning
confidence: 99%
“…Using GAG deficient Chinese hamster ovary cells transfected with CCR1 and CCR5, Ali et al [17] demonstrated that surface GAGs increase the concentration of chemokines presented to the CCRs at the molecular level. CCL5 has been shown to bind GAGs with distinct specificity [16] suggesting that CCL5 may be crucial in mediating inflammatory responses. Furthermore, release of a GAG, chondroitin sulfate A, from platelets in vivo blocked CCL5 binding and CCR5 signaling [18].…”
Section: Chemokines Are (Co)stimulatory For T Cellsmentioning
confidence: 99%
“…The binding affinities have been variously reported in the nanomolar or micromolar range for CXCL8, CCL2, CCL3, and CCL5 (14)(15)(16). Chemokines display differences in their strength of interactions with glycosaminoglycans.…”
mentioning
confidence: 99%
“…Chemokines display differences in their strength of interactions with glycosaminoglycans. For example, CXCL8 shows the following range: heparin Ͼ heparan sulfate Ͼ chondroitin sulfate ϭ dermatan sulfate (14). Different chemokines show variation in their affinities for glycosaminoglycans that are not solely based on charge considerations, suggesting selectivity in these interactions (14,17,18).…”
mentioning
confidence: 99%
“…In the CNS GAGs/ proteoglycans can be found as ECM components and in the basement membrane [25,26]. Although specificity/ selectivity in the chemokine/GAG interaction has not been fully elucidated so far, the great variety in GAG structures on the one side and the reported different affinities for GAGs displayed towards chemokines on the other side, suggest that chemokines interact with disease specific GAG structures in vivo [27,28].…”
Section: Ms Is An Inflammatory Disease Of the Central Nervous System mentioning
confidence: 99%